Characterization of the karyotype and accumulation of repetitive sequences in Australian Darling hardyhead Craterocephalus amniculus (Atheriniformes, Teleostei) - Majtánová, Zuzana; Moy, Karl G; Unmack, Peter J; Ráb, Petr; Ezaz, Tariq (PeerJ, 2019)
Belonging to the order Atheriniformes, Craterocephalus is one of the most widespread genera of freshwater fishes in Australia, spanning along the northern coast from central Western Australia to central New South Wales and across the Murray-Darling and Lake Eyre basins. In this study, both conventional cytogenetic techniques (Giemsa, C-banding, CMA3/DAPI staining), and fluorescence in situ hybridization (FISH) with telomeric DNA and rDNA probes were used to examine the karyotypes and other chromosomal characteristics of Darling hardyhead (Craterocephalus amniculus) from New South Wales, Australia. We identified a diploid chromosome number 2n = 48 (NF = 58) in all studied individuals. FISH with rDNA probes showed a nonsyntenic pattern, with signals on one pair of subtelocentric chromosomes for 5S rDNA and one pair of submetacentric chromosomes for 28S rDNA. C-banding displayed the accumulation of constitutive heterochromatin in the centromeric regions of approximately 40 chromosomes. CMA3/DAPI fluorescence staining revealed extremely GC-rich signals in the pericentromeric region of one submetacentric chromosomal pair with size polymorphism. We detected telomeric signals at the end of all chromosomes and no interstitial signals.
Keywords: Fish cytotaxonomy; Chromosomes; Heterochromatin; Telomeres; rDNA; Karyotype; Chromosomal markers; FISH; Atherinidae